Association between Degrees of Malnutrition and Clinical Outcomes among Non-critically Ill Hospitalized Adult Patients with Type 2 Diabetes Mellitus - Ramos, Freyja Diana; Fontanilla, Joy Arabelle; Lat, Reginna Emiliene (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Introduction. Malnutrition among hospitalized patients is highly prevalent. This adversely affects outcomes with longer length of stay (LOS), higher treatment costs and increased mortality. People with diabetes mellitus (DM) are particularly vulnerable to malnutrition and its consequences. Objective. To determine the association of nutritional status with LOS and mortality among adults with Type 2 DM. Methodology. This was a retrospective study of 439 adult patients with type 2 diabetes admitted in the medical ward of a tertiary hospital from January 1, 2018 to December 31, 2018. Demographics, anthropometrics, feeding route, LOS and outcomes were taken from the Clinical Nutrition Service database; biochemical data were taken from the Healthcare System, and were analyzed. Results. In our analysis, 83.8% were found to be malnourished with 50.3% moderately-malnourished (MM) (Nutrition risk level 1-2) and 33.5% severely-malnourished (SM) (Nutrition risk level ³3). BMI category and malnutrition were the significant confounders for LOS. After controlling for BMI, LOS was longer by a mean of 2.2 days in SM compared to well-nourished (WN) patients (95% CI=0.49-3.95, p=0.012). Of the malnourished patients, 6.1% of SM and 0.5% of MM patients died. None of the WN patients died. Feeding route, admitted for neoplasm, low albumin levels and malnutrition were the confounding factors associated with mortality. After controlling for these factors, SM had higher odds of dying compared to MM patients [adjusted OR=8.91 (95% CI=1.04-76.18, p=0.046)]. Conclusion. Among hospitalized non-critically ill adult patients with type 2 diabetes, SM patients but not MM patients had significantly longer LOS compared to WN patients, and greater degrees of malnutrition were associated with higher mortality.